Interferon-induced protein with tetratricopeptide repeats 5 of black fruit bat (Pteropus alecto) displays a broad inhibition of RNA viruses - Clayton, Emily; Atasoy, Mustafa O.; Naggar, Rania F. El; Franco, Ana Cláudia; Rohaim, Mohammed A.; Munir, Muhammad (Frontiers in Immunology, 2024)
Bats are natural host reservoirs and have adapted a unique innate immune system that permits them to host many viruses without exhibiting symptoms. Notably, bat interferon stimulated genes (ISGs) have been shown to play antiviral roles. Interferon induced protein with tetratricopeptide repeats 5 (IFIT5) is a well-characterised ISG in humans with antiviral activities against negative-sense RNA viruses via inhibiting viral transcription. Here, we aim to investigate if Pteropus alecto (pa) IFIT5 (paIFIT5) possess the ability to inhibit negative-sense RNA viruses. Initially, gene syntenic and comparative structural analyses of multiple animals highlighted a high level of similarity between Pteropus alecto and human IFIT5 proteins. Our results showed that paIFIT5 was significantly inducible by viral and dsRNA stimulation. Transient overexpression of paIFIT5 inhibited the replication of vesicular stomatitis virus (VSV). Using minireplicon and transcription reporter assays, we demonstrated the ability of paIFIT5 specifically to inhibit H17N10 polymerase activity. Mechanistically, we noticed that the antiviral potential of paIFIT5 against negative sense RNA viruses was retributed to its interaction with 5'ppp containing RNA. Taken together, these findings highlight the genetic and functional conservation of IFIT5 among mammals.